THE PUBLIC-PRIVATE PARTNERSHIP: UNUTILIZED DEVELOPMENT POTENTIAL OF RURAL AREAS - Vasiljević, Zorica; Dedeić, Predrag (Economics of Agriculture, 2011)
This paper analyzes a number of issues related to the possibility of development of underdeveloped rural areas through public-private partnership which is established at the local level and regions. In addition to financial aid that may come from central government or EU funds, self-organization in this specific form of partnership can give certain results. The authors draw the belief that this form of cooperation and synergy of public and private sectors is significant potential for sustainable rural development. The importance of this paper comes from the fact that Serbia strengthens the belief that the initiative for investment and development must come primarily from local and regional levels, together with using all available resources, regardless of form of ownership. Economic development is always a phenomenon of a multidisciplinary nature (economic, technical, urban, demographic, sociological, political ones,…), so its analysis can involve many aspects. The analysis in this study included the relevant regulatory and institutional framework important for the public-private partnerships, as well as the experiences and models of cooperation that have been successfully used both by developed countries and developing ones. The authors point out that there is still no legislation directly governing public-private partnership, neither there are significant business experiences and case law. Besides the fair presentation of the current situation in this area it is also point at the ways for further actions.